Notes on the genus Neopseustis Meyrick with description of a new species from China (Lepidoptera: Neopseustidae) - Liao, Cheng-Qing; Chen, Liu-Sheng; Huang, Guo-Hua (Zootaxa, 2021)
A new species, Neopseustis rectagnatha Liao, Chen & Huang sp. nov., is described from the Nanling Mountains, China. The photos of the adults, male and female genitalia, and abdominal special structures are presented. The new species is similar to N. meyricki Hering, 1925 and N. sinensis Davis, 1975, but it can be distinguished easily by characters in the male genitalia as the straight gnathos and the lateroposterior process of anellus h-type bifurcated. Key to males of all species of Neopseustis Meyrick, 1909 and some biological information are also given. Molecular analysis based on COI sequences is used to infer the relationship of the new species within Neopseustis.